2006
DOI: 10.1007/s00439-005-0126-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population

Abstract: A systematic study on the structure and function of Glucose-6-phosphate dehydrogenase (G6PD) variations was carried out in China. A total of 155,879 participants were screened for G6PD deficiency by the G6PD/6PGD ratio method and 6,683 cases have been found. The prevalence of G6PD deficiency ranged from 0 to 17.4%. With informed consent, 1,004 cases from 11 ethnic-based groups were subjected to molecular analysis. Our results showed the followings: (1) The G6PD variants are consistent across traditional ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 35 publications
4
76
1
1
Order By: Relevance
“…In contrast, G6PD Canton, another common variant in Chinese population, was never seen in the Sikka nor in the Ende. Many surveillances of G6PD deficiency in Chinese, Thai, and Malay populations, conducted in China, Taiwan, Thailand, Malaysia and Singapore, have revealed that frequency of G6PD Canton is higher than that of G6PD Kaiping (Chang et al 1992;Huang et al 1996;Chiang et al 1999;Ainoon et al 1999;Nuchprayoon et al 2002) or they are almost equal (Chiu et al 1993;Quak et al 1996;Ainoon et al 2003Ainoon et al , 2004Jiang et al 2005Jiang et al , 2006. Therefore, it is interesting why G6PD Canton was not detected in the Sikka or Ende populations.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, G6PD Canton, another common variant in Chinese population, was never seen in the Sikka nor in the Ende. Many surveillances of G6PD deficiency in Chinese, Thai, and Malay populations, conducted in China, Taiwan, Thailand, Malaysia and Singapore, have revealed that frequency of G6PD Canton is higher than that of G6PD Kaiping (Chang et al 1992;Huang et al 1996;Chiang et al 1999;Ainoon et al 1999;Nuchprayoon et al 2002) or they are almost equal (Chiu et al 1993;Quak et al 1996;Ainoon et al 2003Ainoon et al , 2004Jiang et al 2005Jiang et al , 2006. Therefore, it is interesting why G6PD Canton was not detected in the Sikka or Ende populations.…”
Section: Resultsmentioning
confidence: 99%
“…The high frequency distribution of G6PD Kaiping, a common variant in Chinese population, in the Sikka, Flores Islands is a rather unexpected fi nding (Kawamoto et al, 2006). In contrast, Jiang et al (2006) characterized that G6PD Canton was never seen in the Sikka, Flores Islands nor in the Ende, Timor Islands, although many studies revealed that G6PD Canton in China, Taiwan, Thailand, Malaysia, and Singapore is found at higher than or almost equal in frequency to G6PD Kaiping in those countries. Bioinformatics is needed to discover the genetic relationships between mutations that are common in Indonesia, and those found in China, India and the Middle East.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the molecular tests are also applied to detect Mediterranean mutation (563C>T), a common in the Southern Europe and Viangchan mutation (871G>A), the main kind in Lao and Cambodian widely (Joly, 2010). In China where has the close genetic interaction with Viet Nam, nine mutations (A95G, G392T, G487A, A493G, C592T, C1024T, C1360T, G1376T, G1388A) occupying more than 90% of G6PD deficient cases have been determined (Jiang et al, 2006;Yan et al, 2006). In these mutations, the Canton mutation (G1376T) and Kaiping mutation (G1388A)-two missense mutations in type 2 -occupying 53.8% have been successfully diagnosed by the HRM analysis (high resolution melting analysis) (Yan et al, 2010).…”
Section: Hrm For G6pd Deficiencymentioning
confidence: 99%